Do Financing Constraints Lead to Incremental Tax Planning? Evidence from the Pension Protection Act of 2006* - Campbell, John L.; Goldman, Nathan C.; Li, Bin (Contemporary Accounting Research, 2021)
ABSTRACT Over the past three decades, academic research has sought to understand how cash shortfalls impact a firm's ability to take all available value‐increasing investment projects. We investigate whether firms facing greater financing constraints turn to tax strategies that generate lower cash effective tax rates (ETRs) to mitigate the adverse effect of these financing constraints. We use the Pension Protection Act of 2006 (PPA 2006) as an exogenous shock to financing constraints for pension firms, but not for other firms. Using a difference‐in‐differences research design, we predict and find that pension firms experience a decrease in their cash ETRs by 1.8%–2.4% after the PPA 2006, relative to other firms. These cash tax savings mitigate the investment shortfall brought about by financing constraints by 19%. We also predict and find that the decline in cash ETRs is greater among firms more adversely affected by the PPA 2006. Our paper sheds light on the direction, causality, and economic magnitude of the association between financing constraints and tax planning activities. We also provide insight into the role of tax planning activities within firms' broader corporate business strategies in responding to financing constraints.